1993
DOI: 10.1016/0735-6757(93)90078-p
|View full text |Cite
|
Sign up to set email alerts
|

The effect of sodium bicarbonate administration on the vasopressor effect of high-dose epinephrine during cardiopulmonary resuscitation in swine

Abstract: Sodium bicarbonate is administered during cardiopulmonary resuscitation (CPR) for the treatment of systemic acidemia. However, the effect of administering standard-dose sodium bicarbonate on the vasopressor effect of epinephrine is unknown. This study compared the effects of sodium bicarbonate or normal saline on the vasopressor effect of epinephrine in 18 pigs. After 10 minutes of unassisted ventricular fibrillation, CPR was started using a pneumatic chest compression device. Two minutes after the start of CP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

1995
1995
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 22 publications
0
4
0
1
Order By: Relevance
“…It is unknown whether the protective effect of NaH co 3 in the current study is generalizable to cardiac arrest in general. Previous nonhyperkalemic animal studies have reported conflicting results with some studies showing harm (18, 19), some finding no effect (20–22), and some finding a beneficial effect (23–26) of NaH co 3 administration. Clinical studies in patients without hyperkalemic cardiac arrest have been equally conflicting with three small, randomized trials finding no effect, and observational studies demonstrating different results (27–33).…”
Section: Discussionmentioning
confidence: 98%
“…It is unknown whether the protective effect of NaH co 3 in the current study is generalizable to cardiac arrest in general. Previous nonhyperkalemic animal studies have reported conflicting results with some studies showing harm (18, 19), some finding no effect (20–22), and some finding a beneficial effect (23–26) of NaH co 3 administration. Clinical studies in patients without hyperkalemic cardiac arrest have been equally conflicting with three small, randomized trials finding no effect, and observational studies demonstrating different results (27–33).…”
Section: Discussionmentioning
confidence: 98%
“…62These findings were challenged by Bleske et al who argued that the doses used in the earlier studies were much larger than those in clinical practice (1 mEq/kg) 63…”
Section: Buffers In Cardiac Arrestmentioning
confidence: 97%
“…Much of the evidence against the routine use of bicarbonate is based on animal studies and may have limited applicability to humans as the doses of bicarbonate used have often been high. [93][94][95] One prospective randomised controlled trial has been reported on the use of buffers in patients with out of hospital cardiac arrest. 96 The buffer used was Tribonat (a mixture of sodium bicarbonate, trometamol, disodium phosphate, and acetate).…”
Section: Buffer Agentsmentioning
confidence: 99%